Newton’s “Experimental Philosophy” - Shapiro, Alan E. (Estudios de Filosofía, 2007)
Newton abjured using the term “experimental philosophy,” widely used in Restoration England at the start of his career, until 1712 when he added a passage to the General Scholium of the Principia that brie y expounded his anti-hypothetical methodology. Drafts for Query 23 of the second edition of the Opticks (1706) (which became query 31 in the third edition), however, show that he had intended to introduce the term to explain his methodology earlier. Newton introduced the term for polemical purposes to defend his theory of gravity against the criticisms of Cartesians and Leibnizians but, especially in the Principia, against Leibniz himself. “Experimental philosophy” has little directly to do with experiment, but rather more broadly designates empirical science. Newton’s manuscripts provide insight into his use of “experimental philosophy” and the formulation of his methodology, especially such key terms as “deduce,” “induction,” and “phenomena,” in the early eighteenth century.